Suspended sand transport in different conditions of temperature and salinity - Chung, Dang Huu (Vietnam Journal of Mechanics, 2005)
A study on the action of temperature and salinity on the distribution of suspended sand concentration and transport rate has been carried out through a lDV model with a proposed formula of the kinematic viscosity. Five tests of the data sets from the Delta flume with three different cases of temperature and salinity were used for the simulation. The results of computation showed that the vertical distributions of suspended sand concentration depend on salinity and specially, on temperature. When temperature increases or salinity decreases, the settling process of particles occurs faster. For fine sand, the discrepancy on transport rates due to temperature or salinity decreases with wave height. For coarse sand, the effect of temperature and salinity is not much affected by the wave height. The lDV model showed good ability to simulate the time-averaged suspended sand concentrations and hence the suspended transport in the ripple regime, provided that the reference concentration near the bed and the vortex-related mixing are represented with sufficient accuracy. Therefore; it can be used effectively to study the behaviour of some physical parameters on the transport.